Loquat Growing in the Florida Home Landscape - Jonathan H. Crane; M. Lilia Caldeira (EDIS)
Revised! HS-5, a 9-page fact sheet by Jonathan H. Crane and M. Lilia Caldeira, provides homeowners with an expanded and reorganized basic reference for growing loquat in the home landscape. Tables include information on selected cultivars for Florida, cultural practices by month, fertilizer program, pulp characteristics, and nutritional values. Included in the Master Gardener Handbook. Published by the UF Horticultural Sciences Department, October 2005. Reviewed November 2006.